The mesotendineum of the superficial digital flexor tendon (SDFT). (18th July 2022) - Orth, Saskia; Staszyk, Carsten; Rijkenhuizen, Astrid B. M.
Summary: Background: It is a common assumption that the mesotendineum of the SDFT creates an extrasynovial space within the tendon sheath. Thus, an incision of the palmar/plantar annular ligament (PAL) in this area should not result in the opening of the digital flexor tendon sheath (DFTS). Objective: To identify differences in the conformation of the mesotendineum of the SDFT, which do not allow for an extrasynovial midline desmotomy of the PAL in every horse. Study design: A prospective study on horse cadaver limbs. Methods: A total of 60 cadaver limbs from 15 horses were taken and divided into two groups. A midline or a lateral desmotomy of the PAL was performed. An opening of the DFTS in the course of midline desmotomy was investigated, the attachment of the mesotendineum at the SDFT and the PAL was measured. A correlation between the conformation of the mesotendineum and the opening of the DFTS was investigated. Results: Four different types of the mesotendineum could be detected. Type 1 and 2 both include a continuous mesotendineum, but differ in their width. Type 3 and 4 show a discontinuous attachment of the mesotendineum. In type 3, there is no attachment in its distal part, and in type 4, the interruption of the attachment is seen in its central part. Using the conventional desmotomy in the midline, the DFTS was entered in 50% of the limbs because of a thin, interrupted or a missing attachment at the distal part of the mesotendineum. Main limitations: The relatively low number of cases and the heterogeneous distribution of breeds did not allow for substantial statistical analysis. Conclusion: This study shows that an extrasynovial midline dissection of the PAL is not always guaranteed due to different anatomical conformations of mesotendineum.